Does IFRS convergence really increase accounting qualities? Emerging market evidence - Fuad, Fuad (2019)
Purpose – This study aims to examine whether International Financial Reporting Standards (IFRS) convergence process adds value to the accounting quality dimensions, including accruals quality, earnings smoothing, timely loss recognition and earnings persistence. Design/methodology/approach – It analyzes the hypothesis of accounting quality changes in post-IFRS convergence by using the univariate and multivariate statistics. Particularly, the authors rely on paneldata analyses using industrial companies’data from 2008 until 2014, comprising 3,861 firm-years observations, in Indonesia. Findings – The results indicate that there is no conclusive evidence that all accounting quality dimensions including accruals quality, earnings smoothing, timely loss recognition and earnings persistence increased inpost-IFRS convergence. Practical implications – The findings of this study may help regulators and standard setters to considerfuture adoption of IFRS, mostly to figure out the best “formula” to increase the usefulness of accounting information in post-IFRS convergence. Originality/value – Rather than doing piece meal work, the current study focuses on IFRS convergence on a broader aspect of accounting quality dimensions. It also focuses on the convergence process of IFRS as analternative of full adoption, which has been the focus of many research studies.